Normal Pressure Hydrocephalus Following Myodil Myelography - Ezgi Akar; Mehmet Ufuk Akmil (International Journal of Integrated Health Sciences, 2015)
Objective: Fat-saturated contrast agent-enhanced myelography was used for the purpose of diagnosing most spinal lesions from the beginning of the 19th century until the end of the 20th century. Myodil was among the agents used for many years for this purpose.Methods: A rare long-term complication of myodil myelography is presented with a cerebrospinal fluid (CSF) absorption disorder occurring years after myelography that caused a secondary normal pressure hydrocephalus.Results: A case of normal pressure hydrocephalus with a slowly developing clinical picture that emerged years after a ventriculoperitoneal shunt for a myodil myelography 25 years ago due to suspicion of lumbar spinal stenosis was treated. Conclusions: Many acute and chronic complications of fat-saturated contrast agents were reported. Because of these complications and with the technological developments in due course, these agents are replaced by computerized tomography (CT), magnetic resonance imaging (MRI), or hydrophilic contrast agents.Keywords: Normal pressure hydrocephalus, myelography, myodil DOI: 10.15850/ijihs.v3n1.406